Oral microbiota and periodontitis severity among Hispanic adults - Ortiz, Ana P.; Acosta-Pagán, Kimil T.; Oramas-Sepúlveda, Carla; Castañeda-Avila, Maira A.; Vilanova-Cuevas, Brayan; Ramos-Cartagena, Jeslie M.; Vivaldi, José A.; Pérez-Santiago, Josué; Pérez, Cynthia M.; Godoy-Vitorino, Filipa (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Periodontitis, one of the most common bacterial infections characterized by chronic inflammation, is also known to be a risk factor for chronic conditions, including cardiovascular disease and cancer. This inflammation is driven by an altered microbiota with an increase in pathogenic bacteria. We evaluated the association between oral microbiota and periodontitis severity in high-risk Hispanics . Methods: This cross-sectional study recruited 134 sexually active participants aged 21 to 49 years old from STI Clinics in Puerto Rico. A periodontal examination, saliva collection, and an interviewer-administered questionnaire were performed. Periodontal severity was categorized as: having no disease, mild, and moderate/severe and BOP and tooth loos was noted. Saliva samples were collected for genomic DNA extraction, downstream 16S rDNA amplification sequencing, and bioinformatics analyses. Results: The structure, composition, and diversity of bacterial communities differed significantly according to periodontal severity. The richness and overall diversity also differed between participants without periodontitis and participants with some level of periodontal disease. A higher abundance of Prevotella, Veillonella, or Treponema was attributed to periodontal disease and Aggregatibacter to severe bleeding on probing, while Neisseria was found in higher abundance in healthy participants, decreasing its levels with drinking, smoking, and oral sex practices. Conclusions: Our findings indicate that dysbiosis occurs as periodontal disease progresses, and both alcohol consumption and smoking habits pose risk factors for oral dysbiosis. These results are of public health and clinical impact, as several bacteria identified could serve in the future as biomarkers for periodontitis and oral cancer risk.